Road traffic deaths: A retrospective analysis (2009–2019) in the north of the Italian region Emilia Romagna. (2nd January 2022) - Anzillotti, L.; Dagoli, S.; Calò, L.; Maglietta, G.; Cecchi, R.
Abstract: Objective: International literature and several national studies demonstrate that alcohol and illicit drugs impair driving abilities, diminishing the level of attention, and cause traffic accidents. In Italy, driving under the influence of alcohol or drugs is regulated by Articles 186 and 187 of the National Street Code, which defines penalties and fines for the convicted. The aim of this study was the collection of all available data from 2009 to 2019 focusing on deaths related to road accidents in the Unit of Legal Medicine of Department of Medicine and Surgery at the University of Parma, in order to assess any consumption of alcohol, illicit drugs, and medicinal drugs among drivers. Methods: Data were retrieved from autopsy reports found at the Unit of Legal Medicine of Parma University related to 327 subjects who died following road accidents in the Italian areas of Parma, Reggio–Emilia, and Piacenza. The population was divided into subgroups according to age, gender, crash time, and drug positivity. Results: Those in the age group 46 to 65 years old were involved in the most accidents, whereas the category with fewest members included subjects under 26 years old. The majority of road accidents occurred during the daytime and on weekends. Among the toxicological investigations carried out (only for drivers), the highest prevalence was found for alcohol (43.1%), followed by illicit drugs (14.4%) and medicinal drugs (7.8%). The prevalence of alcohol and illicit drugs in combination was 11.8%. Regarding subjects positive for alcohol and illicit drugs in combination, 44.4% had a blood alcohol concentration (BAC) > 1.5 g/L and overall, in 61.1% of the total cases a BAC > 0.81 g/L was detected. Conclusions: Our results are in line with national and international studies highlighting the prevalence of high BAC levels in most of the cases. Confirmation analyses on blood collected from people who died following road accidents showed levels of BAC above 0.8 g/L (threshold for penal sanctions) in the majority of the subjects who tested positive for alcohol. They also revealed cocaine, cannabis, and benzodiazepines as the most common illicit drugs and medicinal drugs used, respectively, as demonstrated in several international studies.